The Relationship Between Gut Microbiome Features and Chemotherapy Response in Gastrointestinal Cancer - Li, Ningning; Bai, Chunmei; Zhao, Lin; Sun, Zhao; Ge, Yuping; Li, Xiaoyuan (Frontiers in Oncology, 2021)
Objective The prognosis of advanced gastrointestinal cancer is poor. There are studies indicating that gut microbes might have the predictive ability to evaluate the outcome of cancer therapy, especially immunotherapy. There is limited evidence to date on the influence of microbes on chemotherapeutic response. Design In total, 130 patients with advanced or metastatic esophageal (n=40), gastric (n=46), and colorectal cancer (n=44) were enrolled. We included 147 healthy people as controls and used 16S rRNA sequencing to analyze the fecal microbiota. Results Significant differences in the abundance of fecal microbiota between patients with gastrointestinal cancer and controls were identified. The abundance of Bacteroides fragilis, Escherichia coli, Akkermansia muciniphila, Clostridium hathewayi, and Alistipes finegoldii were significantly increased in the patient group. Faecalibacterium prausnitzii, Roseburia faecis, Clostridium clostridioforme, Blautia producta, Bifidobacterium adolescent, and Butyricicoccus pullicaecorum taxa were significantly more abundant in the controls. The amount of R. faecis in non-responders (NR) was more likely to decrease significantly after chemotherapy, while the amount mostly increased in responders (R) (P=0.040). The optimal abundance variation of R. faecis may be a predictor for distinguishing patients with PD from those with non-PD in all patients with gastrointestinal cancer, with a sensitivity of 75.0% and a specificity of 93.9%. Conclusion The gut microbiome of patients with esophageal cancer, gastric cancer, and colorectal cancer differs from those of healthy people. The abundance alteration of R. faecis in patients with GI cancer might be a predictor of chemotherapy efficacy.